Clinical outcomes and health care utilization pre- and post-laparoscopic radiofrequency ablation of symptomatic fibroids and laparoscopic myomectomy: a randomized trial of uterine-sparing techniques (TRUST) in Canada - Rattray DD; Weins L; Regush LC; Bowen JM; O'Reilly D; Thiel JA (Dove Medical Press, 2018)
Darrien D Rattray,1 Laura Weins,2 Lexy C Regush,2 James M Bowen,3,4 Daria O’Reilly,3,4 John A Thiel1,2 1Department of Gynecology, Regina General Hospital, Regina, SK, Canada; 2Department of Obstetrics, Gynecology and Reproductive Sciences, University of Saskatchewan, Regina, SK, Canada; 3Department of Health Research Methods, Evidence and Impact, Faculty of Health Sciences, McMaster University, Hamilton, ON, Canada; 4Programs for Assessment of Technology in Health (PATH), Research Institute of St Joe’s Hamilton, Hamilton, ON, Canada Objective: The objective of this study was to compare laparoscopic ultrasound-guided radiofrequency ablation of fibroids (Lap-RFA) and laparoscopic myomectomy in terms of 1) health care utilization and 2) serious complication rates. The secondary objectives were comparison of subject responses to validated symptom and quality-of-life questionnaires. We hypothesized that Lap-RFA health care utilization and clinical outcomes would not be worse than those of laparoscopic myomectomy in the aggregate. Patients and methods: Post-market, randomized, prospective, multicenter, longitudinal, non-inferiority interventional comparative evaluation of health care utilization and clinical outcomes in premenopausal women with symptomatic uterine fibroids who desired uterine conservation was conducted. Both procedures were planned as outpatient day surgeries. Health care resource utilization was measured during the procedure day and at 1 week, 1 and 3 months post-surgery. Symptom severity and quality of life were based on patients’ responses to the Uterine Fibroid Symptom Severity and Quality-of-Life Questionnaire, EuroQol-5D-visual analog scale general health status and menstrual impact questionnaires, and time from work. Results: Forty-five participants provided written informed consent and were enrolled (Lap-RFA, n=23; myomectomy, n=22) in Canada. Hospitalization time (primary endpoint) was 6.7±3.0 hours for the Lap-RFA group and 9.9±10.7 hours for the myomectomy group (Wilcoxon, p=0.0004). Intraoperative blood loss was lesser for Lap-RFA subjects: 25.2±21.6 versus 82.4±62.5 mL (p=0.0002). Lap-RFA procedures took lesser time than myomectomy procedures: 70.0 versus 86.5 minutes (p=0.018), and Lap-RFA required −34.9% (130 fewer) units of surgical equipment. At 3 months, both cohorts reported the same significant symptom severity reduction (−44.8%; p<0.0001). Lap-RFA subjects also took lesser time from work: 11.1±7.6 versus 18.5±10.6 days (p=0.0193). One myomectomy subject was hospitalized overnight after experiencing a 20-second asystole during the procedure. One Lap-RFA subject underwent a reintervention. The combined per patient direct and indirect costs of the two procedures were comparable: Lap-RFA (CAD $5,224.96) and myomectomy (CAD $5,321.96). Conclusion: Compared to myomectomy, Lap-RFA is associated with significantly lesser intraoperative blood loss, shorter procedure and hospitalization times, lesser consumption/use of disposable and reusable surgery equipment, reduced health care resource utilization, and faster return to work through 3 months posttreatment. Direct and indirect costs of Lap-RFA and myomectomy are comparable. Keywords: Acessa, radiofrequency ablation, fibroids, laparoscopy, myomectomy, ultrasound